Pelatihan Pembuatan Animasi Untuk Kalangan Pengajar Dalam Upaya Meningkatan Ketrampilan Dibidang Teknologi - Yulianton, Heribertus; Santi, Rina Candra Noor; Ningsih, Dewi Handayani Untari; Wismarini, Theresia Dwiati; Supriyanto, Edy (Fakultas Teknologi Informasi dan Industri Unisbank, 2024)
Macromedia Flash is an application that can be used to create animations. The use of Macromedia Flash is still not used optimally for developing learning media. Macromedia Flash itself is a software application used to create animations and is an application program commonly used in creating multimedia. The convenience of this application can be used to create and edit animations to make them more interesting and beautiful. For learning media, teaching materials can be used to beautify the teaching materials that will be given by students, students who can follow lessons well and not in a monotonous manner can hopefully improve student achievement results